PERSEPSI KE-BIOMIMIKRI-AN RUANG TERBUKA HIJAU BERDASARKAN PENGALAMAN PENGUNJUNG DI TAMAN SAMARENDAH - Sari, Dharwati P.; Utomo, Pandu K.; Wahyuni, Sri; Salasa, Bernardo Sandrini (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
One of Samarinda City's green open space, Taman Samarendah carries the concepts of culture and environment. This research departs from the observation that Taman Samarendah contains components of the biomimicry concept approach. The purpose of the research is to learn how park visitors perceive the design of biomimicry in relation to what they regard at Taman Samarendah. The method used is mixed methods with grounded theory as its foundation. As a result, the garden elements associated with the biomimicry criteria, the most respondents chose form criteria with a percentage of 36.27%, followed by function criteria 22.55%, while other criteria were relatively insignificant. In addition, measuring the strength of the biomimicry impression per criterion, the results were obtained in the form of: function criteria were in the highest position perceived by visitors as the 'most biomimicry' thing from Taman Samarendah with a score of 3.31, followed by form criteria (3.23), material criteria (3.14), construction criteria (3.13), and process criteria (3.07).